2006
DOI: 10.1124/dmd.106.012708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Goldenseal (Hydrastis canadensis) and Kava Kava (Piper methysticum) Supplementation on Digoxin Pharmacokinetics in Humans

Abstract: ABSTRACT:Phytochemical-mediated modulation of P-glycoprotein (P-gp) and other drug transporters may give rise to many herb-drug interactions. Serial plasma concentration-time profiles of the P-gp substrate, digoxin, were used to determine whether supplementation with goldenseal or kava kava modified P-gp activity in vivo. Twenty healthy volunteers were randomly assigned to receive a standardized goldenseal (3210 mg daily) or kava kava (1227 mg daily) supplement for 14 days, followed by a 30-day washout period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…Gurley et al (86) found that kava is not a potent modulator of P-gp in humans. The inducible transcription factor nuclear, factor kappaB (NFkappaB), regulates immune, inflammatory, and carcinogenic responses.…”
Section: Alteration Of Cytochrome P450 Metabolizing Isozymes-it Has Bmentioning
confidence: 99%
“…Gurley et al (86) found that kava is not a potent modulator of P-gp in humans. The inducible transcription factor nuclear, factor kappaB (NFkappaB), regulates immune, inflammatory, and carcinogenic responses.…”
Section: Alteration Of Cytochrome P450 Metabolizing Isozymes-it Has Bmentioning
confidence: 99%
“…Ranunculaceae) has a history of folk medicine use in the treatment of gastrointestinal disturbances, urinary disorders, skin ailments and various infections [2,4]. A clinical trial showed that goldenseal did not change the disposition of digoxin, suggesting that this herb has no effect on P-glycoprotein [105]. Although one study did not yield the same conclusions [106], convincing clinical evidence suggests that adverse herb-to-drug interactions may result with concomitant ingestion of goldenseal and drugs that are metabolized by CYP3A4 or CYP2D6 [14,17,107,108].…”
Section: Clinical Interactions Between Herbs and Conventional Drugsmentioning
confidence: 99%
“…Goldenseal supplement was purchased from Nature's Resource (Lot #0/10184; Mission Hills, CA). This brand of Goldenseal was chosen because it was used in previous human studies conducted by our group (Gurley et al, 2007(Gurley et al, , 2008bGupta et al, 2009) and the manufacturer (Pharmavite, LLC) claims to follow current good manufacturing practices in the sourcing and manufacture of its products. Each goldenseal was independently determined to contain 13 mg of hydrastine.…”
Section: Methodsmentioning
confidence: 99%